Solid waste management – what’s the Malaysian position - Mohd Nasir Hassan,; Theng , Lee Chong; Mizanur Rahman,; Mohd Nazeri Salleh,; Zulina Zakaria ,; Muhamad Awang, (Environmental Management Society, Malaysia, 2001)
Solid waste management is becoming more critical in Malaysia due to unresolved problems and the emergence of new issues both at local and international levels. The most fundamental aspects still unsolved is the basic information about our waste i.e. data on the source and types of solid wastes and its physical, chemical and biological characteristics. This article highlights the basin issues of waste generation rate and its composition together with aspects such as the level of waste disposal, the prospects of capital-intensive waste treatment technologies especially incineration, and the inherent issue of recycling. This article also presents the latest information about the physical composition of Malaysian wastes, together with the values on bulk density, moisture content and the calorific value. Recycling issue is discussed in terms of roles to be played by major key players in the recycling chain, efforts to improve the rate of recycling and finally the cost and benefit aspects of recycling